Explorando os conceitos da radiação do corpo negro desde a física clássica até a moderna por meio da metodologia Peer Instruction - Marinho, Ludimilson Mota (2025)
The present research aims to investigate evidence of improved learning among Youth and Adult Education (EJA) students regarding the classical and modern descriptions of black-body radiation, resulting from the integration of the Peer Instruction (PI) methodology into the teaching-learning process. To achieve this objective, a qualitative study with an action research approach was conducted with 28 students in the 11th stage of the 2024 academic year of the Youth and Adult Education (EJA) program at the Antônio da Encarnação Filho State School, within the Amazonas State education network. Aligned with the theoretical framework of learning, the collected data were obtained through conceptual learning verification tests administered before, during, and after the lessons. The data analysis was performed using Content Analysis, with student responses as the unit of analysis. The data were categorized into Conceptual Understanding, Knowledge Application, and Opinion Change. The research concluded that the PI teaching methodology is effective in optimizing classroom time, promoting student engagement, and gradually improving their state of understanding and ability to apply the content. Consequently, students are able to progress from a partial understanding or skill after the pre-class phase to demonstrating comprehension or application skills during and after the lesson.